Solvency of Insurans Islam TAIB Sdn Bhd - Jair, Osman (2005)
The solvency of insurance companies has been the major issue in the insurance industry. According to A.M. Best (Swiss Re sigma no 1/2000) in the US between the year 1969 to 1998 there have been 683 insolvencies. However, the topic of solvency is seldom being mentioned in the Islamic insurance (takaful) literature. Takaful as an insurance business of cooperation in concept with mutual agreement has grown in a period of only 20 years and it has only been in Brunei Darussalam for the past 12 years. The modified Mudharabah Model with profit sharing concept has been normally accepted especially in the South East Asia region. The position of Mudharabah (profit sharing) concept is debatable especially in the Middle East on its compliancy with Shariah (Islamic Law). The study on the effect of Mudharabah onto capital of the takaful company and its fundamentality of Mudharabah concept in the takaful business has been conducted. The regulators of insurance and takaful companies play an important role in ensuring the solvency of any companies. The good solvency regulation will provide an early warning system to the ailing insurance and takaful companies and the regulators' intervention will provide an early remedial plan and prevent financial disaster for the insurance and takaful companies and their customers.